Electrometric investigations on the formation of cerium(III) tungstates as a function of pH - Prasad, Shiva; de Brito, André Luiz Fiquene; Muniz, Ana Cristina Silva; Leite, Valderí Duarte (Eclética Química, 2000)
The course of reaction between cerium(III) nitrate and different sodium tungstates (Na2WO4, Na10W12O41 and Na6W12O39) has been followed by means of pH and conductometric titrations between the reactants at different pH levels, in aqueous and alcoholic media, with each of the reagents alternatively used as titrant. The electrometric experiments provide definite evidence of the formation of normal-Ce2O3.3WO3 and para- 5Ce2O3.36WO3 tungstates of cerium in the vicinity of pH 6.2 and 5.3. The formation of normal tungstate is almost quantitative and the pH titrations offer a simple means for determination of cerium(III) or tungstate solutions at suitable concentrations and pH range.